2013
DOI: 10.1007/s00284-013-0447-x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Vibrio cholerae Bacteriophages Isolated from the Environmental Waters of the Lake Victoria Region of Kenya

Abstract: Over the last decade, cholera outbreaks have become common in some parts of Kenya. The most recent cholera outbreak occurred in Coastal and Lake Victoria region during January 2009 and May 2010, where a total of 11,769 cases and 274 deaths were reported by the Ministry of Public Health and Sanitation. The objective of this study is to isolate Vibriocholerae bacteriophages from the environmental waters of the Lake Victoria region of Kenya with potential for use as a biocontrol for cholera outbreaks. Water sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 17 publications
1
5
0
1
Order By: Relevance
“…1). The virion morphology suggested that the phages belong to the family Myoviridae, order Caudovirales, as previously described (Maina et al 2014). Genomic features and primary classi cation of VP4, VP6, VP18, and VP24:…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…1). The virion morphology suggested that the phages belong to the family Myoviridae, order Caudovirales, as previously described (Maina et al 2014). Genomic features and primary classi cation of VP4, VP6, VP18, and VP24:…”
Section: Resultssupporting
confidence: 64%
“…Since V. cholerae is a natural inhabitant of aquatic environments (Almagro-Moreno and Taylor 2013;Lutz et al 2013), these environments are favorable for exploring candidate therapeutic bacteriophages. Indeed, several tailed bacteriophages, especially from family Myoviridae, were detected during environmental surveys in regions where outbreaks were reported, e.g., Peru (Talledo et al 2003), Kolkata (Sen and Ghosh 2005) and Kenya (Maina et al 2014). Of note, tailed bacteriophages are the most dominant viruses in the aquatic environment (Madhusudana Rao and Lalitha 2015;Letchumanan et al 2016), which makes them a good initial candidate for screening, but will require elaborate efforts for their isolation.…”
Section: Introductionmentioning
confidence: 99%
“…Current understanding of environmental phages has largely come from those which are aquatic in origin, however, freshwater phages are understudied in comparison to their marine counterpart and isolated phages are often cyanophages [ 7 9 ]. To date, few studies exist pertaining to specific characterization of freshwater phages that do not infect cyanobacteria [ 10 ], rendering them particularly under-represented in databases such as RefSeq. Representation of freshwater phages is of considerable importance when one considers the close proximity these environs often have to human activity: for example, the potential for anthropogenically-mediated pollution (e.g., sewage outfall), and, when considering Lake Michigan in particular, the use of freshwater as a source of drinking water and recreation.…”
Section: Resultsmentioning
confidence: 99%
“…An increase in phage numbers in the environment was also correlated with an increase in V. cholerae lytic bacteriophage in patient stool samples, with one of the predominant bacteriophage species belonging to the Myoviridae family ( Seed et al, 2011 ). Environmental surveys have detected Myoviridae in regions where cholera outbreaks have occurred, such as Peru ( Talledo et al, 2003 ), Kolkata ( Sen and Ghosh, 2005 ), and Kenya ( Maina et al, 2013 ). Control of V. cholerae by phage is supported by a continuous culture experiment, which suggests that V. cholerae populations may be influenced by phage to a larger extent than by nutrient limitation ( Wei et al, 2011 ).…”
Section: Top-down Control By Predatory Micrograzersmentioning
confidence: 99%